Uncovering Wolbachia Diversity upon Artificial Host Transfer - Schneider, Daniela I. (Public Library of Science, 2013)
The common endosymbiotic Wolbachia bacteria influence arthropod hosts in multiple ways. They are mostly recognized for their manipulations of host reproduction, yet, more recent studies demonstrate that Wolbachia also impact host behavior, metabolic pathways and immunity. Besides their biological and evolutionary roles, Wolbachia are new potential biological control agents for pest and vector management. Importantly, Wolbachia-based control strategies require controlled symbiont transfer between host species and predictable outcomes of novel Wolbachia-host associations. Theoretically, this artificial horizontal transfer could inflict genetic changes within transferred Wolbachia populations. This could be facilitated through de novo mutations in the novel recipient host or changes of haplotype frequencies of polymorphic Wolbachia populations when transferred from donor to recipient hosts. Here we show that Wolbachia resident in the European cherry fruit fly, Rhagoletis cerasi, exhibit ancestral and cryptic sequence polymorphism in three symbiont genes, which are exposed upon microinjection into the new hosts Drosophila simulans and Ceratitis capitata. Our analyses of Wolbachia in microinjected D. simulans over 150 generations after microinjection uncovered infections with multiple Wolbachia strains in trans-infected lines that had previously been typed as single infections. This confirms the persistence of low-titer Wolbachia strains in microinjection experiments that had previously escaped standard detection techniques. Our study demonstrates that infections by multiple Wolbachia strains can shift in prevalence after artificial host transfer driven by either stochastic or selective processes. Trans-infection of Wolbachia can claim fitness costs in new hosts and we speculate that these costs may have driven the shifts of Wolbachia strains that we saw in our model system.